A legal mechanism to prevent the spread of HIV/AIDS - Oksana V. Topchii, Roman V. Veresha, Alexander N. Dzhuzha, Dmitry M. Tychina, (Opción, 2020)
Modern regulation of social diseases requires consideration of the social context and criminogenic phenomena, which substantiate the necessity for a comprehensive approach. Combining medical, economic and legal aspects will build a legal infrastructure for the protection of HIV/AIDS patients and reduce discrimination in society while maintaining the safety of a healthy population. The aim of this article is to analyze the legal mechanism of HIV/AIDS prevention in Ukraine and in the world. The results demonstrate the basics of health and legal education as the most important means of preventing HIV/AIDS.